Modification of Triangle Run Exercise to Improve the Endurance of Cricket Athlete - Memet Muhamad; Mia Kusumawati; Aridhotul Haqiyah; Herlina Ulfah Rosadi (STKIP Singkawang, 2019)
This study aims to determine the effect of modification of triangle run exercises on endurance of male cricket athletes in Bekasi. This research method uses the experimental method. The population and sample in this study were all male cricket athletes with 14 people. The researcher used the total sampling technique or the whole to be sampled. The results of this study indicate that the factor of triangle run training can have a significant effect on endurance in male cricket athletes in Bekasi with the results of tcount = 5.24 in p > 0.05.